Time-Series Single-Cell RNA-Seq Data Reveal Auxin Fluctuation during Endocycle. (16th December 2019) - Torii, Kotaro; Kubota, Akane; Araki, Takashi; Endo, Motomu
Abstract: Appropriate cell cycle regulation is crucial for achieving coordinated development and cell differentiation in multicellular organisms. In Arabidopsis, endoreduplication is often observed in terminally differentiated cells and several reports have shown its molecular mechanisms. Auxin is a key factor for the mode transition from mitotic cell cycle to endocycle; however, it remains unclear if and how auxin maintains the endocycle mode. In this study, we reanalyzed root single-cell transcriptome data and reconstructed cell cycle trajectories of the mitotic cell cycle and endocycle. With progression of the endocycle, genes involved in auxin synthesis, influx and efflux were induced at the specific cell phase, suggesting that auxin concentration fluctuated dynamically. Such induction of auxin-related genes was not observed in the mitotic cell cycle, suggesting that the auxin fluctuation plays some roles in maintaining the endocycle stage. In addition, the expression level of CYCB1;1, which is required for cell division in the M phase, coincided with the expected amount of auxin and cell division. Our analysis also provided a set of genes expressed in specific phases of the cell cycle. Taking these findings together, reconstruction of single-cell transcriptome data enables us to identify properties of the cell cycle more accurately.